2018
DOI: 10.1016/j.prostaglandins.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of isolevuglandin-protein adduct formation in inflammation and hypertension

Abstract: Inflammation has been implicated in the pathogenesis of hypertension and recent evidence suggests that isolevuglandin (IsoLG)-protein adducts play a role. Several hypertensive stimuli contribute to formation of IsoLG-protein adducts including excess dietary salt and catecholamines. The precise intracellular mechanisms by which these hypertensive stimuli lead to IsoLG-protein adduct formation are still not well understood; however, there is now evidence implicating NADPH-oxidase derived reactive oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 70 publications
(106 reference statements)
0
18
0
Order By: Relevance
“…The study by Hevia et al found that ablation of CD11c 1 antigen presenting cells prevented hypertension in an AngII1 high salt diet murine model (53). A few proposed antigens include isolevuglandin protein adducts (54,55), heat shock protein 70 (56,57), and Toll-like receptor (TLR) 4 or 2 activators such as C-reactive protein (58), uric acid (59), and others (60).…”
Section: T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Hevia et al found that ablation of CD11c 1 antigen presenting cells prevented hypertension in an AngII1 high salt diet murine model (53). A few proposed antigens include isolevuglandin protein adducts (54,55), heat shock protein 70 (56,57), and Toll-like receptor (TLR) 4 or 2 activators such as C-reactive protein (58), uric acid (59), and others (60).…”
Section: T Cellsmentioning
confidence: 99%
“…52 The study by Hevia et al, found that ablation of CD11c + antigen presenting cells prevented hypertension in an AngII+ high salt diet mouse model. 53 A few proposed antigens include isolevuglandin protein adducts, 54,55 heat shock protein 70, 56,57 and toll-like receptor (TLR) 4 or 2 activators such as C-reactive protein 58 , uric acid 59 , and others. 60 Experimental evidence suggests that such molecules may individually or collectively contribute to the role of T cells in hypertension; however, the presence of over 3000 unique TCR sequences in angiotensin II-induced hypertensive mice indicates that clonal expansion may not be occurring due to antigen presentation and recognition.…”
mentioning
confidence: 99%
“…The resultant isoLG-modified protein proteolytically cleaved and presented as an antigen recognized as foreign by the immune system, driving an inflammatory response that contributes to cardiovascular morbidity in a variety of diseases including heart failure and hypertension [ 29 , 30 ]. While isoLG adducted peptides are a well-described phenomenon in both mice and humans [ 12 ], to date the sequence or sequences of residues comprising this family of neoantigens remains undetermined. To infer which residues in an MHC-I presented epitope may favor lysine adduction, we generated a hypothetical peptide with the minimum two key anchor residues [ 31 ] for MHC-I H-2D b (asparagine at P5 and leucine at P9) and alanine residues (chosen for their unobtrusive side chain) elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we illustrate that the model scores calculated by Rosetta FlexPepDock ab-initio correlate well with predicted peptide binding affinities generated by a NetMHCpan, a popular sequence-based prediction method [ 3 ]. Finally, we demonstrate the protocol’s ability to recapitulate peptide backbone structure and binding affinity changes for actual and theoretical peptides containing a variety of NCAAs, including phosphopeptides derived from tumor antigens, the well-characterized glycosylated peptide GP392 isolated from lymphocytic choriomeningitis virus, and isolevuglandin adducted peptides (important drivers of inflammation in cardiovascular disease) [ 12 ]. The ability to use non-canonical amino acids in the Rosetta FlexPepDock protocol can provide useful insights into critical amino acid positions where the post-translational modification enables or disrupts interactions with receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Protein covalent adducts are formed upon exposure to reactive chemical agents (mainly electrophiles) from internal or external exposures. Regardless of their nature, the possibility of identifying protein covalent adducts is of outmost importance due to their profound impact induced at both the molecular and cellular level, ultimately leading to the development of a wide range of deleterious health outcomes, including cancer, cardiovascular and autoimmune diseases [1,2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%